Pediatric kidney transplant recipients with and without underlying structural kidney disease have a comparable risk of hospitalization associated with urinary tract infections - Spiwak, Elizabeth; Nailescu, Corina; Schwaderer, Andrew (Frontiers in Pediatrics, 2022)
Introduction Urinary tract infections (UTIs) are a common and potentially serious kidney transplant complication. Pediatric kidney transplants are potentially at increased risk for UTIs when structural kidney disease is the underlying end-stage kidney disease (ESKD) etiology. The objective of this manuscript is to determine if children with structural kidney disorders are more prone to UTIs post kidney transplant. Materials and methods Hospitalizations for pediatric kidney transplant recipients were retrospectively reviewed over a 4-year period for UTIs in the diagnostic codes. The patient’s age, sex, graft age, underlying diagnosis for cause of ESKD, symptoms at presentation, urinalysis results, and urine culture results were recorded. UTI rates, febrile UTI rates, and UTI rates in the 1st year post-transplant were compared between children with ESKD due to structural vs. non-structural kidney disease. Results Overall, 62 of 145 pediatric patients with kidney transplants accounted for 182 hospitalizations for kidney transplant complications over the 4-year study period. UTIs were components of 34% of the hospitalizations. Overall, UTI rates, febrile UTI rates, and UTI rates for the 1st year post kidney transplant were comparable for children with vs. without structural ESKD etiologies. Conclusion Urinary tract infections are frequent components of hospitalizations for pediatric kidney transplant recipients. Children with and without structural kidney disease as an ESKD etiology have similar UTI rates indicating that UTI susceptibility is primarily due to the transplant process and/or medication regimens. UTIs represent a potentially modifiable risk factor for pediatric kidney transplant complications.